Pengaruh hard skill dan soft skill terhadap kinerja karyawan - Marsha, Savhira Ursila Marsha (Jurnal Ilmu Manajemen, 2024)
Employees are the main asset in an organization and have a strategic role as thinkers, planners and controllers of organizational activities. To achieve high performance, it is necessary to increase optimal work and utilize the potential of human resources owned by employees to achieve organizational goals. Therefore, this research topic is focused on the skills/competencies (hard skills & soft skills) possessed by employees in state-owned companies engaged in the electricity sector. This study aims to analyze and examine the effect of hard skills and soft skills on employee performance. Quantitative research methods with primary data sources will be used in this study. The sampling technique uses a census / full sample with a total population of 66 employees from all divisions of state-owned companies engaged in the electricity sector. Statistical analysis of research using Structural Equation Model (SEM) - Partial Least Square (PLS) with the help of smart pls software version 4. The results of the study explain that hard skills have a significant positive effect on employee performance, soft skills have a significant positive effect on employee performance, and there is a simultaneous or joint influence between hard skills and soft skills on employee performance in one of the state-owned companies engaged in electricity. This research means that if the company wants to improve employee performance, employee’s competency skills must be qualified in both soft and hard skills.